Comparative corrosion characteristics of automotive materials in Jatropha biodiesel - Ahmmad, Md. Shahabuddin; Masjuki, Haji Hassan; Kalam, Md. Abul (Taylor & Francis, 2018)
This study investigated the corrosion characteristics of widely used automotive materials: copper (Cu), aluminum (Al) and stainless steel (SS) in Jatropha biodiesel. The corrosion rate of the materials was measured by the weight loss and changes in the surface morphology using immersion test in biodiesel. Before and after the immersion test, fuel samples were characterized by the change in chemical composition, viscosity, density, and water content. Experimental results revealed that Cu had the highest corrosion rate, while SS had the lowest. The main fatty acids observed in the tested biodiesel were oleic (44.6 wt %), linoelic (31.9 wt %), Palmitic (14.6 wt %), and Stearic (7.6 wt %). Apart from linoelic acid, the compositions of all other acids were increased after the immersion test of 1600 h. Also, the viscosity, density, and water content of the fuel samples were increased after the immersion test. However, these properties were within the maximum standard limit except water content.